The promised neverland. Volume 20, Beyond destiny - Shirai, Kaiu (Shonen Jump manga., 2021)
"Life at Grace Field House had been good for Emma and her fellow orphans. While the daily studying and exams they had to take were tough, their loving caretaker provided them with delicious food and plenty of playtime. But when they discover the horrifying truth about why they are being kept at the orphanage, their lives change forever ... Back at Grace Field House, Emma faces Peter with the future of the demon world hanging in the balance. Meanwhile, something unexpected is happening in the demon capital. Can the children finally escape to the human world? And what fate awaits Emma at the end of her long journey?"--Back cover